2012
DOI: 10.1021/ef301000k
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Burning Velocity of Propane/CO2/N2–Air Mixtures at Elevated Temperatures

Abstract: The laminar burning velocity of pure and diluted high-temperature propane−air mixtures is extracted from the planar flames stabilized in the preheated mesoscale diverging channel. The experiments were carried out for a range of equivalence ratios of 0.7 ≤ Φ ≤ 1.3 and mixture temperatures of 370−650 K. The effect of dilution using CO 2 and N 2 gases (up to 40%) on C 3 H 8 −air burning velocity is also studied. Experiments complimented with computational studies of experimental conditions confirm that the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 27 publications
5
47
0
Order By: Relevance
“…1. A mesoscale channel with a 10° divergent angle, and inlet dimension of 25 mm × 2 mm is used as referred by [7]. The channel is made up of fused quartz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1. A mesoscale channel with a 10° divergent angle, and inlet dimension of 25 mm × 2 mm is used as referred by [7]. The channel is made up of fused quartz.…”
Section: Methodsmentioning
confidence: 99%
“…These flames were planar in both crosswise and depth direction of the channel. Other details of the setup and method can be found in [7]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, on-line or semi-online application of such micro reactors as micro tasters in combustion systems (e.g., internal combustion engines) can upgrade the conventional combustion systems to the intelligent systems. In this regard, several efforts have been made by Maruta and co-workers [1][2][3][4][5][6][7][8], Liu et al [9], and Kumar and coworkers [10][11][12] research teams. They showed that micro and meso-scale reactors can be efficient devices which can somehow evaluate the burning characteristics of various fuel-air mixtures.…”
Section: Introductionmentioning
confidence: 99%